REJUVENASI PARADIGMA DAKWAH DI ERA 4.0 - Mohammad Darwis (Institut Agama Islam Syarifuddin Lumajang, 2019)
This article discusses rejuvenation of Islamic da'wah paradigm in the fourth industrial revolution era, by critically examining the process of social change in society. The era developes technology, while bringing positive and negative effects to society. The public will inevitably face the impact of Industry 4.0, in the form of political, cultural, economic, and ideological aggression. This will further marginalize and disqualify the traditional structures of established communities. Likewise the development of technology as intended also becomes a challenge to the da'wah movement, both concrete and ideological. The emergence of science and technology in this era could have a destructive effect on the da’wah movement and the process of broadcasting Islamic missions to the public. Likewise the emergence of various understandings and ideologies can shift the existence of da'wah, which in turn will push the scope and pace of the da'wah movement. Therefore, in this area, the da’wah movement is required to be able to provide new paradigms that are able to transfer messages of Islamic teachings to the public, so that the existence of Islamic da'wah can always be maintained. Based on the description above, this article describes the challenges and opportunities of da'wah in era 4.0, how to find a new paradigms, the significance of Islamic da'wah in response to technological developments, and the reconstruction of da'wah in era 4.0. Then, at the end of this articles, there is a recommendation about how to do effective da’wah in the fourth industrial revolution era. Key Words: Paradigm of Da'wah, Da'wah, The Fourth Industrial Revolution Era, Rejuvenation